First thought, then reason: the case of Escalas (1923) - Ávalos Salas, Eduardo Mijaíl (2023)
Criticism of Cesar Vallejo’s narrative has interpreted Escalas (1923) as a hermetic text that was the product of the Peruvian bard’s first approach to the narrative genre. As a consequence, Escalas has been studied to understand other Vallejian texts, but not its own organicity. The purpose of this paper is to briefly map the origin of the hermetic label of Escalas and to place the epigraph that the opening is the key to its reading, since it is considered that this contains the sense of the avant-garde character of Escalas. In addition, some stories will be analyzed, both from the «Cuneiforms» section and from the «Wind Choir». For this, the contributions of George Lakoff and Mark Johnson will be used as a theoretical framework, as well as the classification of the styles of thought of Giovanni Bottiroli.